(untitled) (Journal of Economic Research & Business Administration, 2016)
In article questions of decrease in consumer demand against increase of the income of the population in Kazakhstan are considered. There is a replacement of level of the highest requirements with the level of the lowest requirements. Devaluation of tenge, inflation, big dependence on import, etc. are the reasons of it. Decrease in consumer demand can lead to further deterioration of an economic condition of the country. The purpose of article to show how there is a change of a consumer demand in the conditions of financial and economic crisis. As methodological base in work the tools of the economic theory are used. Detection of specifics of a consumer demand in the Kazakhstan economy in the conditions of the unstable institutional environment became the main result of research. The economic system is a set of the interconnected elements therefore in the integrated context of efficiency of economic system it is necessary to consider the aggregated indicators among which the special role is played by cumulative consumer demand. The state economic policy can promote development of consumer demand.